THE EFFECT OF FERTILIZERS ON GROWTH, CONCENTRATION OF NAPHTHOQUINONES AND ANTIMYCOBACTERIAL ACTIVITY OF EUCLEA NATALENSIS (EBENACEAE) - Bapela, J.; Meyer, M.; Toit, E. D.; Lall, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The effect of Nitrogen: Phosphorus: Potassium (NPK) (2:1:2 (44)) fertilizers on growth, content of bioactive naphthoquinones (shinanolone, 7-methyljuglone, diospyrin, isodiospyrin and neodiospyrin) and antimycobacterial activity was investigated in seedlings of Euclea natalensis grown under shade and in field conditions. Seedlings were subjected to three differential fertilization regimes (Treatment 1 at 10 g/l, Treatment 2 at 20 g/l and Treatment 3 at 40 g/l). Naphthoquinones were quantified using High Performance Liquid Chromatography (HPLC). The bioactivity of root extracts from seedlings was tested against Mycobacterium smegmatis and M. tuberculosis. Treatment 2 enhanced the vegetative performance of seedlings grown under shadehouse conditions (P<0.001). A significant correlation was found between the concentration of shinanolone (P<0.01), isodiospyrin (P<0.5) and neodiospyrin (P<0.5) with fertilization in seedlings grown under field conditions. Treatment 2 increased the content of neodiospyrin (P<0.5) in seedlings under shadehouse conditions. Extracts acquired from field-grown seedlings were more active against strains of M. smegmatis with a lowest MIC value of 0.78 mg/ml. Extracts from the Control group and Treatment 1, which had less applied fertilizers, were more active against strains of M. tuberculosis with MIC value of 10 µg/ml. The study indicated that subjecting seedlings to controlled environments coupled with higher levels of fertilizers could have a negative impact on the antimycobacterial activity of E. natalensis.